Bilateral High-Grade Sertoli–Leydig Cell Tumors with Gallbladder Metastasis Presenting as Obstructive Jaundice - Tejo Jayadi; Hanggoro Tri Rinonce; Lili Ananta Saputra; Theresia Hening Dwi Ambarwati; Merari Panti Astuti; Sutaryanu Sutaryanu (Indonesian Socety of Obstetrics and Gynecology, 2026)
Introduction: Sertoli-Leydig cell tumor (SLCT) is a rare ovarian sex cord-stromal tumor.High-grade SLCT is more aggressive and potentially metastasizes, generally through expansion to the peritoneum or lymphovascular metastasis. Metastases to the walls of vesica fellea are very rare. Case description: A 52-year-old woman with heartburn for one week, accompanied by icteric eyes, nausea, vomiting, watery pale diarrhea for five days, and dark brown urine. Laboratory of all liver function were elevated, CEA slightly increased CEA, and CA-125 normal. Ultrasound and MSCT of the abdomen examination exhibited a solid mass of ovaries. MRCP showed multiple stones in the vesica fellea accompanied by cholangitis and obstructive jaundice. The clinical diagnosis was suspected of ovarian cancer with cholelithiasis and cholecystitis, complicated by jaundice is established. The patient underwent TAH-BSO surgery and cholecystectomy. The histopathological examination of the left and right ovaries revealed poorly differentiated, diffuse, and partially tubule-looking Sertoli-Leydig cells in hypercellular and hypocellular ovarian tumors. Polymorphic tumor cells, pleomorphic nuclei, partially with mucin-containing cytoplasm, form a signet ring. Immunohistochemicals of calretinin and inhibin were positively expressed, while EMA and CK were negatively expressed. High-grade SLCT was established as a definitive diagnosis. Histopathological examination of the vesica fellea showed a concluding secondary tumor from the ovary. Conclusion: SLCT incidence is <0.5% of ovarian tumors. Grade and histopathology type determine its nature. High-grade tumor prognosis is inferior serous carcinoma, signet-ring stromal tumor, and gastrointestinal adenocarcinoma metastases were the differential diagnoses because of histopathological morphology similarity. This may be the first case of bilateral high-grade SLCT with metastases to the vesica fellea causing obstructive jaundice.